Limitations and Measures in Outsourcing Projects to Geographically Distributed Offshore Teams - Akhbar, R.; Hassan, M.F. (2010)
Latest global social, economic and technological changes have given birth to a new generation of software engineering practice. Traditional approaches of software development have become less popular. Software development by centrally located in-house teams has slowly been replaced by geographically distributed offshore teams. As such project outsourcing to geographically distributed offshore teams has become a popular and profitable practice. Although it has a number of positive aspects, disadvantages of outsourcing to distributed offshore teams far out-weighted its advantages. This paper identifies those limitations associated with this trend and recommends respective measures to improve the process to overcome them. Real projects outsourced to distributed offshore teams have been exercised and analyzed to identify the limitations and deriving respective measures. The paper suggests that the success of project management activities is dependent on reducing the risk factors and the capability of the project managers to manage the issues involved.